Analisis Faktor Penyebab Kiriman Gagal Antar Pada PT. Pos Indonesia Drop Center Soreang Kabupaten Bandung Jawa Barat - Allysha Maharani Dewi; Tiris Sudrartono (Ekonomis: Journal of Economics and Business, 2022)
This research purposely to know the factors that affect the failed shipments at PT. Pos Indonesia Drop Center Soreang Bandung Regency, West Java. This research used Quantitative Descriptive Methode with explanation data using Check Sheet, Pareto Chart and Fishbone Diagram. The sample used delivery data from Juli-September 2021. The Result of the analysis show that the main cause of failed shipment at PT. Pos Indonesia Drop Center Soreang Bandung Regency, West Java is an Unclear/Uncomplete Address followed by seven factors such as Unknown Address, Recipient Moved, Rejected by Recipient, Empty House, Clogged Address, Recipient Died and Cause of Force Majeure. To minimize this factors, PT. Pos Indonesia (Persero) provides standards and target for failed shipments. It was found that the average rate of failed shipment during the research was 5,7%. This research show that the company has not reached the maximum target for failed shipments which is 3%. As for suggestions for companies to minimize the causes of failed shipments by increasing supervision of writing addresses in accordance with applicable SOP (Standar Operating Procedures) and always re-checking when sending letters or goods.